2021
DOI: 10.1080/09640568.2021.1952857
|View full text |Cite
|
Sign up to set email alerts
|

EIA decision-making and administrative justice: an empirical analysis

Abstract: Environmental impact assessment (EIA) is implemented in most countries as an administrative procedure. In this context, it is subject to the principles of administrative justice. However, to date, no empirical research has been conducted to determine the extent to which EIA decisions comply with the principles of administrative justice. In this paper, empirical data from 42 EIA cases in South Africa are used to establish EIA compliance with the administrative justice principles of lawfulness, procedural fairne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…To address the aim of this article 42 EIA cases that were previously reviewed for conformance to administrative justice principles (Alberts et al 2021b) were now also reviewed against specially designed key performance indicators (KPIs) relating to EIA report substance, that is to say the substantive quality of the information provided in the EIA reports -see Tables 1 and 2. Alberts et al (2021b) found that in terms of conformance to administrative justice principles of lawfulness, reasonableness and procedural fairness…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To address the aim of this article 42 EIA cases that were previously reviewed for conformance to administrative justice principles (Alberts et al 2021b) were now also reviewed against specially designed key performance indicators (KPIs) relating to EIA report substance, that is to say the substantive quality of the information provided in the EIA reports -see Tables 1 and 2. Alberts et al (2021b) found that in terms of conformance to administrative justice principles of lawfulness, reasonableness and procedural fairness…”
Section: Methodsmentioning
confidence: 99%
“…A distinction can however be made between 'administratively correct' EIA decisions and 'good' EIA decisions (Alberts et al 2021b) KPIs were chosen that are empirically measurable and for which data could be obtained from EIA case files. The KPIs addressed South African minimum legal requirements and international best practice for EIA report substance, based on an adapted and contextualised Lee and Colley method (Adapted from Alberts et al, 2020;Alberts et al 2021a;Sandham et al 2008aSandham et al , 2020 -see Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations